Description of two new Jujubinus species (Gastropoda: Trochidae) from the Sicily Channel, with notes on the Jujubinus curinii species complex - Smriglio, Carlo; Di Giulio, Andrea; Mariottini, Paolo (Zootaxa, 2014)
Based on shell characters, two new species of the gastropod family Trochidae, Jujubinus eleonorae n. sp. and Jujubinus trilloi n. sp., from the Sicily Channel are described. Shells of the new taxa were collected in the lower infralittoral of the Skerki and Talbot Banks, respectively. The new taxa are compared with Jujubinus curinii Bogi & Campani, 2005, morphologically the most closely related species.